Participatory Learning and Action for Sustainable Rural Development in India - A Case Study of Didhsari Village, Uttarkashi, Uttarakhand - Gangopadhyay, D.; Mukhopadhyay, A. K. (Journal of Rural Development, 2010)
For any development facilitator, a potential paradox can arise when assisting in self-reliant participatory development. This occurs when the facilitator tries to help and encourage people to develop themselves and in doing so undermines their self-reliance and sustainability, the very aim of development. Participatory Learning and Action (PLA) exercise was carried out during 25 to 29 April, 2009 at Didhsari, Uttarkashi, Uttarakhand, India. Some of the critical factors like socio-economic condition of the village including present status of agriculture, education and health, poverty, unempolyment and livelihoods of the people and people’s perception on the Panchayati Raj Institutions were studied and analysed. Besides, a few self-sustainable and employment generation programmes were identified based on societal needs and an action plan was proposed through participatory approaches. The study would be helpful for the planners and administrators not only in better realisation of the socio-economic condition of the villagers but also in successful implementation of the proposed integrated approaches for sustainable rural development in Didhsari and surrounding villages.